Uptake, yield of neoplasia, and adverse effects of flexible sigmoidoscopy screening. Issue 4 (1st April 1998) - Atkin, W S; Hart, A; Edwards, R; McIntyre, P; Aubrey, R; Wardle, J; Sutton, S; Cuzick, J; Northover, J M A
Abstract : Background —A multicentre randomised controlled trial to evaluate screening by "once only" flexible sigmoidoscopy (FS) for prevention of bowel cancer is in progress. Aims —To pilot the trial protocol examining rates of attendance, yield of neoplasia, and adverse effects. Subjects —A total of 3540 subjects aged 55–64 years in Welwyn Garden City (WGC) and 19 706 in Leicester (LE). Methods —Subjects responding positively to an "interest in screening" questionnaire were randomised to invitation for screening or control arms. Small polyps were removed during screening. Colonoscopy was undertaken for high risk polyps (more than two adenomas, size at least 1 cm, villous histology, severe dysplasia, or malignancy). The remainder were discharged. Results —In WGC and LE respectively, 59% and 61% indicated an interest in screening, of which 74% and 75% attended. Adenomas were detected in 10% and 9%, respectively, and cancers in 7 per 1000 (in both centres), 55% at Dukes's stage A. The colonoscopy referral rate was 6% in both centres. Mild, short lived bleeding occurred in 3%. One person died following surgery. Conclusions —Compliance rates, yield of adenomas, and referral rate for colonoscopy were as expected, but cancer detection rates were higher. Adverse effects following sigmoidoscopy or colonoscopy were mild and transient, but there was one postoperative death. A randomised trial is necessary to evaluate fully the risks and benefits of this intervention.